Method for manufacturing welded stainless steel coated with hydrogen barrier film
Through mechanical polishing and electrolytic polishing treatment, combined with electrolytic polishing liquid containing phosphoric acid and methsulfate, a hydrogen barrier film is formed, which solves the problem that it is difficult for the welding part to achieve the same hydrogen barrier function as the non-welded part, and achieves the efficient hydrogen barrier performance of the welding part.
Patent Information
- Application Number
- JP2023187344
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2025-05-15
- Estimated Expiration
- 2043-11-01
AI Technical Summary
The prior art is difficult to effectively apply hydrogen barrier coating on the welded portion to ensure that it has the same hydrogen barrier function as the non-welded portion.
Through mechanical polishing and electrolytic polishing treatment, the welding surface is ensured to be smooth, and then electrolytic polishing is performed using an electrolytic polishing solution containing phosphoric acid and methsulfuric acid to form a hydrogen barrier film. The method includes the formation, curing and treatment steps to ensure uniformity and density of the hydrogen barrier film.
The same hydrogen barrier performance of the welded part and the non-welded part is achieved, which significantly reduces the hydrogen penetration rate and improves the corrosion resistance and strength of the welded part.
Smart Images

Figure 2025075886000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a welded stainless steel coated with a hydrogen barrier film, and more particularly to a method for producing a welded stainless steel coated with a hydrogen barrier film obtained by passivating a metal oxide film formed by a wet process. [Background technology]
[0002] Hydrogen is expected to be an alternative energy source to fossil fuels. Hydrogen penetrates metal surfaces and embrittles them, so hydrogen embrittlement is a problem in the storage and transportation of high-pressure hydrogen in liquefied hydrogen tanks and hydrogen stations. Furthermore, piping and container components are often welded, and hydrogen embrittlement at welded parts is also a problem. For this reason, methods to impart hydrogen embrittlement resistance to piping, container components, and welded parts are being studied.
[0003] Patent Document 1 discloses stainless steel (SUS304) having excellent corrosion resistance and hydrogen embrittlement resistance, which is obtained by passivating a metal oxide film formed by a wet process that is cost-effective and requires low processing and equipment costs, and a manufacturing method thereof. However, it does not disclose a specific manufacturing method for covering welded parts of stainless steel with a chromium oxide film that has the same hydrogen barrier function as non-welded parts. Patent Document 2 discloses a new electropolishing solution and electropolishing method that provide excellent surface smoothness for stainless steel in electropolishing, which is a pretreatment for forming a passivation film, in the production of stainless steel with excellent corrosion resistance by passivating a metal oxide film formed on the surface of the stainless steel by a wet process that is cost-effective with low processing and equipment costs. However, it does not disclose a specific production method for covering welded parts of stainless steel with a chromium oxide film that has the same hydrogen barrier function as non-welded parts.
[0004] Non-Patent Documents 1 and 2 disclose stainless steel (SUS304) with hydrogen barrier function, which is formed by passivating a metal oxide film formed by a wet process mainly based on the INCO method. However, these disclosures concern the hydrogen barrier properties of the surface of general stainless steel (SUS304), and do not disclose welded parts, which are presumed to be most susceptible to the effects when used as a film to enhance the environmental barrier properties of large structures such as chemical plant equipment and piping containers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6869495 [Patent Document 2] Patent No. 7029742 [Non-patent literature]
[0006] [Non-Patent Document 1] K. Kawami, B. An, T. Iijima, S. Fukuyama, M. Imaoka, H. Tamai, M. Tamura, A. Kinoshita, T. Tanaka; Proc. ASME Pressure Vessels Piping Conf. p.93260(Am. Soc. Mech. Eng.,2019). [Non-Patent Document 2] K. Kawami, A. Kinoshita, H. Yamanaka. Y. Fukuda, H. Enoki, T. Iijima, S. Fukuyama, R. Tsukane, T. Tanaka, T. Fukutani, Y. Suzuki, H. Tamai, T. Ogi, M. Tamura; Proc. ASME Pressure Vessels Piping Conf. p.80128(Am. Soc. Mech. Eng., 2022). Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention proposes a method for manufacturing welded stainless steel in which the welded parts of the stainless steel are covered with a chromium oxide film that has hydrogen barrier properties equivalent to those of non-welded parts. [Means for solving the problem]
[0008] The problem of the present invention can be solved by the following aspects. Specifically,
[0009] (Aspect 1) A method for manufacturing a welded stainless steel coated with a hydrogen barrier film, comprising: a mechanical polishing step of mechanically polishing the welded surface of the welded stainless steel by flat polishing and buffing; an electrolytic polishing step of electrolytically polishing the welded stainless steel surface with the mechanically polished welded surface with an electrolytic polishing solution consisting of phosphoric acid and methanesulfonic acid; and a hydrogen barrier film formation step of forming a hydrogen barrier film on the electrolytically polished welded stainless steel by the Inco method, wherein the arithmetic mean height S of the welded stainless steel after the electrolytic polishing step conforms to ISO25178-6. a This is a method for producing a welded stainless steel coated with a hydrogen barrier coating, characterized in that the thickness (nm) of the welded stainless steel is 1.5 nm or less. The arithmetic mean height S of the welded stainless steel after the electrolytic polishing process conforming to ISO25178-6 a By setting the thickness (nm) to 1.5 nm or less, the hydrogen barrier film can be uniformly coated.
[0010] (Aspect 2) This is a method for producing a welded stainless steel coated with a hydrogen barrier film according to Aspect 1, characterized in that the electropolishing solution containing phosphoric acid and methanesulfonic acid has a phosphoric acid concentration of 25 to 50 vol % and a methanesulfonic acid concentration of 50 to 75 vol %. This is because an electropolishing solution containing phosphoric acid and methanesulfonic acid increases the viscosity of the electropolishing solution, thereby enhancing the effect of electropolishing.
[0011] (Aspect 3) This is a method for producing a welded stainless steel coated with a hydrogen barrier film according to Aspect 1, characterized in that the hydrogen barrier film formation step comprises a film formation step of immersing the stainless steel surface in a treatment liquid consisting of a mixed solution of chromic acid and sulfuric acid to form a chromium oxide film on the stainless steel surface, a hardening treatment step of immersing the chromium oxide film formed in the film formation step in a treatment liquid consisting of a mixed solution of chromic acid and phosphoric acid to harden the chromium oxide film, and a passivation treatment step of immersing the chromium oxide film hardened in the hardening treatment step in a treatment liquid consisting of a passivating agent to passivate the chromium oxide film.
[0012] (Aspect 4) The hydrogen permeability of the welded stainless steel coated with the hydrogen barrier film is 2.0×10 -14 mol / (m 2 ·s·Pa 0.5 )~3.5×10 -14 mol / (m 2 ·s·Pa 0.5 The present invention relates to a method for producing a welded stainless steel coated with a hydrogen barrier coating according to any one of aspects 1 to 3, wherein
[0013] (Aspect 5) This is a method for producing a welded stainless steel coated with a hydrogen barrier film according to any one of Aspects 1 to 3, characterized in that the hydrogen barrier film of the welded stainless steel coated with a hydrogen barrier film by the hydrogen barrier film formation step has unconnected pores of about 10 nm in size formed therein, which function as hydrogen trapping sites. This is because the formation of unconnected vacancies of about 10 nm in size that function as hydrogen trapping sites allows the vacancy interface to act as a hydrogen trapping site, suppressing hydrogen diffusion and improving the hydrogen barrier properties. Effect of the Invention
[0014] According to the present invention, excellent smoothness of the welded stainless steel surface before coating with a hydrogen barrier coating can be achieved by performing mechanical polishing and electrolytic polishing using an electrolytic polishing solution consisting of phosphoric acid and methanesulfonic acid. This removes the welded altered layer (oxide scale) and forms a uniform hydrogen barrier coating. As a result, a welded stainless steel with excellent hydrogen barrier properties can be provided. In addition, in the case of stainless steel that has been coated with a hydrogen barrier film and welded according to the present invention, unconnected pores of about 10 nm in size that function as hydrogen trapping sites are formed in the hydrogen barrier film, and the pore interfaces act as hydrogen trapping sites, suppressing hydrogen diffusion and improving the hydrogen barrier properties. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic diagram showing the appearance of a welded portion before and after mechanical polishing and a prepared welded test piece in the present invention. FIG. [Diagram 2] FIG. 1 is a flow diagram of a process for forming a hydrogen barrier film on a stainless steel that has been subjected to welding according to the present invention. [Diagram 3] 1 is an explanation of a hydrogen permeability measuring device used to measure the hydrogen permeability of a welded stainless steel coated with a hydrogen barrier coating according to the present invention. [Figure 4] 1 is a graph showing the results of measuring the hydrogen permeability Φ of stainless steel that has been coated with the hydrogen barrier coating of the present invention and that has been subjected to welding. [Diagram 5] 1 is a graph showing the element distribution in the depth direction (depth profile) by XPS of a stainless steel coated with the hydrogen barrier film of the present invention and subjected to welding. [Figure 6] 1 shows XPS wide scan profiles of a non-welded portion and a welded portion of a stainless steel that has been coated with a hydrogen barrier coating according to the present invention and that has been subjected to welding processing. [Figure 7] 1 is a microstructure analysis image, obtained by energy dispersive X-ray spectroscopy (TEM-EDS), of a cross section of a coating of stainless steel that has been coated with the hydrogen barrier coating of the present invention and has been subjected to welding processing. [Figure 8] 1 is an elemental mapping image of a cross section of a coating of stainless steel that has been coated with a hydrogen barrier coating according to the present invention and has been subjected to welding processing. [Figure 9] FIG. 2 is an explanatory diagram of the hydrogen permeation mechanism in a welded stainless steel coated with the hydrogen barrier coating of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described below with reference to the embodiments. However, the following description is for the purpose of understanding the present invention and is not intended to limit the present invention.
[0017] The present invention is a method for producing a welded stainless steel coated with a hydrogen barrier film, comprising: a mechanical polishing step of mechanically polishing the welded surface of the welded stainless steel by flat polishing and buffing; an electrolytic polishing treatment step of electrolytically polishing the welded stainless steel surface with the mechanically polished welded surface with an electrolytic polishing solution consisting of phosphoric acid and methanesulfonic acid; and a hydrogen barrier film formation step of forming a hydrogen barrier film on the electrolytically polished welded stainless steel by the Inco method. The following describes the welded stainless steel, the mechanical polishing process, the electrolytic polishing process, and the hydrogen barrier film formation process in that order.
[0018] 1. Welded stainless steel As the stainless steel used for the welded stainless steel of the present invention, stainless steels used for high-pressure storage vessels for storing hydrogen and high-pressure pipelines for transporting hydrogen can be preferably used. Specifically, there are ferritic stainless steels, martensitic stainless steels, and austenitic stainless steels. For high-pressure storage vessels and high-pressure pipelines that require corrosion resistance and high strength, martensitic stainless steels (e.g., 410C, 420, 430, 440C, 440B) and austenitic stainless steels (e.g., 304, 304L, 321, 347, 316L) can be preferably used.
[0019] For welding stainless steel in the present invention, non-consumable electrode gas shielded arc welding, called GTAW (Gas Tungsten Arc welding) such as TIG welding (Tungsten Inert Gas welding) or plasma arc welding, can be suitably used. In TIG welding, a TIG welding torch including a non-consumable electrode, a torch nozzle, and a torch body is used to generate an arc between the non-consumable electrode (-) and the workpiece (+), and welding is performed while melting the workpiece with the heat of the arc to form a molten pool. In addition, during welding, a shielding gas is discharged from the torch nozzle surrounding the electrode, and welding is performed while blocking the atmosphere (air) with this shielding gas. In the TIG welding torch, the cooling effect on the non-consumable electrode reduces the area of the arc generated from the tip of the non-consumable electrode, and the power of the arc increases, resulting in deep penetration.
[0020] 2. Mechanical polishing process (2-1) Surface polishing In the surface polishing, the welded part is subjected to surface polishing processing using a surface polishing device. As the polishing tool, a polishing liquid containing a hard urethane pad and cerium oxide abrasive grains, or a polishing liquid containing a soft urethane pad and cerium oxide abrasive grains (cerium oxide abrasive grains having a smaller average particle size than the cerium oxide abrasive grains may be used) is used. Furthermore, a soft urethane pad and a polishing liquid composition mainly composed of colloidal silica having an average primary particle size of about 20 to 30 nm can be used.
[0021] (2-2) Buffing Buffing is a method of polishing the outer surface of a cloth or nonwoven fabric coated with an abrasive. By polishing a rough and uneven surface several times with different cloth or nonwoven fabrics or abrasives, it is possible to polish the surface from rough to shiny. Types of buffs include cloth buffs, such as sewn buffs, bound buffs, loose buffs, bias buffs, and sisal buffs. Other types of buffs include flap wheels, nonwoven fabric wheels, and wire wheels. These buffs are used according to their intended use. Those made of raised nylon fibers are preferred. Buff abrasives include abrasives that are primarily made of relatively fine abrasive powder, and are mixed uniformly with a medium made of oils and other suitable ingredients.
[0022] 3.Electrolytic polishing process The electrolytic polishing process serves as a pretreatment to remove or reduce surface defects such as oxide films, impurities (non-metallic inclusions), and processing-affected layers on the surface of welded stainless steel, and to form a uniform, dense chromium oxide film with hydrogen barrier properties on the surface of welded stainless steel. In particular, it serves to completely remove oxide scale (process-affected layers) from the welded areas. Electrolytic polishing is a polishing method in which a direct current is applied from an external power source to the metal to be polished as the anode in an electrolytic polishing solution, dissolving the finely irregularities on the metal surface to smooth and polish it. Unlike physical polishing such as buffing, this method has the advantage of not causing any deterioration or work-hardened layers, and the polished surface is clean because there are fewer impurities and contamination. In the anodic polarization curve (Jacquet curve) of an electrolytic polishing bath, there is a constant current (limiting current) range that is independent of the electrode potential. In this limiting current range, a thick, highly viscous anolyte layer (Jacquet layer) is formed near the metal being polished. This anolyte layer (Jacquet layer) is thought to suppress the diffusion of eluted cations, which is how polishing occurs. In other words, the unevenness of the surface of the metal being polished creates a difference in the concentration gradient in the viscous liquid layer, and the diffusion current causes the current to concentrate on the convex parts, which causes the surface unevenness to disappear and polishing to occur.
[0023] (3-1) Electrolytic polishing liquid The electrolytic polishing treatment of the present invention is an electrolytic polishing solution for stainless steel consisting only of phosphoric acid and methanesulfonic acid, characterized in that the phosphoric acid concentration is 25-50 vol% and the methanesulfonic acid concentration is 50-75 vol%. That is, the electrolytic polishing solution for stainless steel subjected to welding processing of the present invention is composed of only water as a solvent and phosphoric acid and methanesulfonic acid as a solute. As shown in Table 2, by using methanesulfonic acid as the solute of the electrolytic polishing solution instead of sulfuric acid with high viscosity, the viscosity of the electrolytic polishing solution can be reduced, and the retention of bubbles generated on the metal surface due to the anode reaction by the electrolytic polishing treatment can be suppressed. In addition, the electrolytic polishing solution does not contain additives such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ester, and glycerin for stabilizing the electrolytic polishing solution because the suppression of the generation of bubbles is more effective in smoothing the metal surface than the stabilization of the electrolyte. Instead of methanesulfonic acid, organic sulfonic acids such as ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, p-phenolsulfonic acid, and vinylsulfonic acid can be selected.
[0024] The composition of the electrolytic solution of the present invention can be selected from the ranges of phosphoric acid concentration of 25 to 50 vol% and methanesulfonic acid concentration of 50 to 75 vol%. By making the methanesulfonic acid concentration equal to or higher than the phosphoric acid concentration, the viscosity of the electropolishing solution can be reduced.
[0025] In the electrolytic polishing process of the present invention, by adopting the above-mentioned electrolytic polishing solution and electrolytic polishing method, the surface roughness of stainless steel that has been welded can be suppressed to 1.5 nm or less (see Table 2). This is because the surface roughness of stainless steel that has been welded affects the hydrogen barrier film formation process described below. Here, "surface roughness" refers to the arithmetic mean height S according to ISO25178-6. a (nm).
[0026] (3-2) Electrolytic polishing method The electrolytic polishing method of the present invention is an electrolytic polishing method that employs the above-mentioned electrolytic polishing solution, and can employ either or both of the pulse voltage application treatment and the micro aeration treatment disclosed in Japanese Patent No. 7029742.
[0027] 4. Hydrogen barrier film formation process The hydrogen barrier film formation process plays a role in forming a chromium oxide film that has hydrogen barrier function on the surface of the welded stainless steel, thereby imparting hydrogen barrier properties to the welded stainless steel. The hydrogen barrier film forming process comprises a film forming process in which the stainless steel surface is immersed in a treatment liquid consisting of a mixed solution of chromic acid and sulfuric acid to form a chromium oxide film, a hardening process in which the chromium oxide film formed in the film forming process is immersed in a treatment liquid consisting of a mixed solution of chromic acid and phosphoric acid to harden the chromium oxide film, and a passivation process in which the chromium oxide film hardened in the hardening process is immersed in a treatment liquid consisting of a passivating agent to passivate the chromium oxide film.
[0028] (4-1) Film formation process The chromium oxide film is formed in a mixed solution of chromic acid and sulfuric acid, which is known as the Inco method (see JP 48-011243 A). The thickness of the formed chromium oxide film is controlled by the potential difference between the anode and the reference electrode. The thickness of the chromium oxide film is more than 200 nm, and preferably 250 nm to 350 nm.
[0029] By controlling the rate at which the chromium oxide film is formed (hereinafter referred to as the "film formation rate"), it is possible to improve the adhesion and uniformity of the film and suppress the occurrence of thin film areas and film defects (pinholes), which are causes of reduced corrosion resistance. The rate of film formation can be controlled by the composition and temperature of the treatment liquid. As for the composition of the treatment liquid, a suitable mixture ratio of sulfuric acid and chromic acid (chromic acid / sulfuric acid) is 15-30 wt / v% chromic acid and 40-50 wt / v% sulfuric acid. By reducing the concentration of chromic acid, the rate of formation of the chromium oxide film that performs the hydrogen barrier function can be slowed down, and the thickness of the chromium oxide film that is formed can be precisely controlled. The temperature of the treatment liquid is 60-90°C. The film formation rate can be controlled by the potential rate (mV / sec). The potential rate is 0.002 to 0.08 mV / sec, preferably 0.005 to 0.065 mV / sec. If the potential rate is less than 0.002 mV / sec, the formation of the chromium oxide film is delayed, resulting in reduced productivity. If the potential rate exceeds 0.08 mV / sec, the thickness of the chromium oxide film formed becomes non-uniform, resulting in thin areas of the coating film and coating defects (pinholes) that cause reduced hydrogen barrier properties. In order to compensate for the rate of formation of the chromium oxide film caused by the reduction in the concentration of chromic acid in the treatment solution, manganese ions (Mn 2+ ) can be added. Manganese salts include manganese chloride (MnCl2), manganese sulfate (MnSO4), manganese nitrate (Mn(NO3)2), etc., and one or more of these can be used. Manganese ions (Mn 2+ The concentration of manganese ions (Mn 2+ If the concentration is less than 0.5 mmol / L, there is no effect of promoting the formation of a chromium oxide film, and manganese ions (Mn 2+ ) If the concentration exceeds 300 mmol / L, insoluble portions will remain, which will affect the formation of the chromium oxide film.
[0030] (4-2) Hardening treatment process The hardening treatment process serves to harden and strengthen the chromium oxide film formed on the surface of the welded stainless steel. In the hardening process, the welded stainless steel on which the chromium oxide film was formed in the film formation process is used as the cathode, and the chromium oxide film is hardened by cathodic electrolysis. The chromium oxide film formed in the film formation process has 10 to 20 nm pores per cm. 2 10 per 11 These voids are the cause of the deterioration of the hydrogen barrier properties, and the voids can be sealed by hardening treatment. It can also strengthen loose coatings. The mixture ratio of chromic acid and phosphoric acid (chromic acid / phosphoric acid) of the hardening treatment liquid is preferably 15-30 wt / v% chromic acid and 0.2-0.3 wt / v% phosphoric acid as a reaction accelerator. Current density: 0.2-1.0 A / dm 2 Do this for 5 to 10 minutes.
[0031] (4-3) Passivation treatment process The passivation treatment step serves to further densify and compact the hardened chromium oxide film, thereby further improving the hydrogen barrier properties of the chromium oxide film.
[0032] (4-3-1) Passivation treatment The passivation treatment is carried out in an aqueous solution containing an oxidizing agent capable of passivating the metal (hereinafter referred to as "passivating agent"). Passivating agents include nitric acid, chromic acid, permanganic acid, molybdic acid, nitrous acid, nitrates (e.g., magnesium nitrate), and chromates (e.g., sodium dichromate). In addition, the addition of sodium dichromate makes the pitting potential, which will be described later, more noble, improving pitting resistance. The amount of sodium dichromate added is preferably 1.5 to 3.5 wt%. The passivation treatment methods include (a) immersion in a solution containing nitric acid or other strong oxidizing agent, and (b) anodic polarization in a solution containing an oxidizing agent. Since the present invention is a wet process, either (a) or (b) can be used. This passivation treatment strengthens the hydrogen barrier properties of the chromium oxide film, which is formed in the film formation process and hardening treatment process and has a thickness of over 100 nm.
[0033] (4-3-2) Sequential passivation treatment The passivation treatment of the present invention is composed of at least two or more independent passivation treatment steps, and the passivation treatment can be carried out sequentially. By carrying out at least two or more independent passivation treatments with different passivation agent compositions, the hydrogen barrier property of the chromium oxide film formed in the film formation step and hardening treatment step and having a thickness of more than 100 nm is improved. EXAMPLES
[0034] Next, embodiments that exhibit the effects of the present invention will be described as examples.
[0035] 1. Stainless steel The stainless steel welded according to the present invention is a welded product of a commercially available austenitic stainless steel SUS3042B finish material (hereinafter referred to as "stainless steel") having the chemical composition shown in Table 1.
[0036] [Table 1]
[0037] 2. Preparation of Welded Stainless Steel A stainless steel piece (40 mm x 60 mm, thickness 0.5 mm) was TIG welded to produce a welded stainless steel (80 mm x 60 mm, thickness 0.5 mm). The welding was performed using a DC TIG welding machine. <Welding conditions> Tungsten electrode Φ1.6mm Argon gas flow rate: 5L / min Welding current 120A (no pulse)
[0038] 3. Mechanical polishing process The welded stainless steel was polished and buffed to a thickness of 0.1 mm, then machined into a circular shape (Φ30 mm) to prepare a welded test piece. Figure 1 shows the appearance of the welded part before and after mechanical polishing, as well as the prepared welded test piece.
[0039] 4.Electrolytic polishing process The welded test pieces were electrolytically polished by changing the electrolyte mixture ratio (E1, E2, E3). The welded test piece that was not electrolytically polished was designated T1. The electrolytes used were phosphoric acid (H3PO4: purity 85 mass%), sulfuric acid (H2SO4: purity 85 mass%), and methanesulfonic acid (CH3SO3H: purity 98 mass%). The viscosity of the electrolyte was measured with a vibration viscometer (SV-10 manufactured by A&D). The welded test piece was immersed in the electrolyte at 343K and simultaneously subjected to a direct current of 20A / dm 2 Electrolytic polishing was performed by anodic electrolysis at 40°C for 3 minutes. After visually checking the metallic luster and the presence or absence of cloudiness, the arithmetic mean height S of a micro area (5 μm × 5 μm) was measured using a scanning probe microscope (Shimadzu SFT-5400) in accordance with ISO25178-6. a (nm) was measured. The electrolytic polishing treatment and physical properties are shown in Table 2.
[0040] [Table 2]
[0041] The electrolyte containing organic acid (methanesulfonic acid) has an arithmetic mean height S a The arithmetic mean height S of the micro-area of the electrolyte consisting of only inorganic acid (sulfuric acid, phosphoric acid) was 5.7 nm (E2) and 1.5 nm (E3). a (nm) was 12.5 nm (E1). The electrolyte containing an organic acid (methanesulfonic acid) provided high smoothness to the test piece after electrolytic polishing. Also, the electrolyte (E3) consisting of phosphoric acid and methanesulfonic acid provided high smoothness to the test piece after electrolytic polishing compared to the electrolyte (E2) containing sulfuric acid.
[0042] 5. Hydrogen barrier film formation treatment FIG. 2 shows a flow chart of the process for forming a hydrogen barrier film on stainless steel that has been subjected to welding according to the present invention. The welded test piece was electrolytically polished (Fig. 2(a)) in an electrolyte (E3) consisting of phosphoric acid and methanesulfonic acid, and then polished at 250 g / dm 3 of chromium oxide (CrO3) and 500g / dm 3 The specimen was immersed in a mixture of sulfuric acid (H2SO4) and 100% sodium hydroxide at 338K for 30min (Fig. 2(b)). Next, the welded test specimens were subjected to a 250g / dm 3 of chromium oxide (CrO3) and 2.5 g / dm 3 The specimen was immersed in a mixture of phosphoric acid (H3PO4) and 1A / dm2 at 338K for 30 min. 2 The solution was subjected to cathodic electrolysis for 10 min at 40°C (Fig. 2(c)). Finally, the welded specimen was immersed in a mixture of 25 vol% nitric acid (HNO3) and 2.5 mass% sodium dichromate (Na2Cr2O7) at 298 K for 15 min, and then immersed in a 50 mass% Mg(NO3)2 aqueous solution at 333 K for 360 min (Fig. 2(d)).
[0043] 6. Hydrogen permeability measurement The hydrogen permeability Φ [mol / (m 2 ·s·Pa 0.5 ) was measured. The hydrogen permeability (Φ) according to this test method can be evaluated using formula (1). Φ=(J d) / (A ΔP 0.5 ) (1) Here, d is the thickness of the test piece, and J is the volume per unit time (permeability) of hydrogen gas that permeates the test piece when there is a partial pressure gradient ΔP between both sides of a test piece with area A. The exponent of the partial pressure gradient ΔP is 0.5 because, when the rate-limiting step of hydrogen permeation is diffusion within the test piece, the amount of hydrogen atoms present in the test piece is proportional to the square root of the hydrogen gas partial pressure according to Sievert's law.
[0044] FIG. 3 is a schematic diagram of a welded test piece equipped with a gold packing and a hydrogen permeability measuring device equipped with the welded test piece. The coating surface of the welded test piece was placed in a hydrogen gas atmosphere of 400 kPa, and the opposite side was reduced in pressure using a pump. The welded test piece was kept at 300°C, and the hydrogen gas that permeated from the coating surface to the opposite side was measured by gas chromatography.
[0045] FIG. 4 is a graph showing the results of measuring hydrogen permeability Φ. The hydrogen permeability Φ of the welded test piece without a coating and the non-welded test piece was 2.51×10 -12 mol / (m 2 ·s·Pa 0.5 ), 2.10×10 -12 mol / (m 2 ·s·Pa 0.5 ), and the hydrogen permeability Φ of the coated welded and non-welded specimens was 2.02×10 -14 mol / (m 2 ·s·Pa 0.5 ), 3.50×10 -14 mol / (m 2 ·s·Pa 0.5 By covering the material with the film, the hydrogen permeability Φ was reduced to 1 / 100. As a result, it was confirmed that the stainless steel that has been subjected to the welding process, which has been subjected to the mechanical polishing process, electrolytic polishing process and film formation process of the present invention, exhibits a hydrogen permeability Φ equal to or greater than that of steel that has not been subjected to welding process, and exhibits hydrogen barrier properties.
[0046] 7. Film structure analysis (7-1) Element distribution in the depth direction The electrolytic polishing modified layer and the coating layer were evaluated by X-ray photoelectron spectroscopy (XPS) to evaluate the element distribution in the depth direction and the bonding state of the compounds using an X-ray photoelectron spectrometer (ULVAC-PHI, Quantera SXM). The XPS measurement conditions were: excitation X-ray monochromatic Al-Kα ray, beam diameter 200 μm, photoelectron detection angle 45°, ion etching 4 kV Ar ion, and raster size 2 × 2 mm. The etching grade was 23.7 nm / min (SiO2 equivalent value).
[0047] Figure 5 is a graph showing element distribution in the depth direction (depth profile) by XPS, (a) a non-welded area before coating, (b) a welded area before coating, (c) a non-welded area after coating, and (d) a welded area after coating. Comparing the non-welded area (a) and the welded area (b) before coating, the welded area (b) has an expanded area with high concentrations of Fe and O, and the oxide scale from welding remains even after mechanical polishing. On the other hand, comparing the non-welded area (c) and the welded area (d) after coating, the Cr concentration from the surface to 290 nm in both the non-welded area (c) and the welded area (d) is about 10 at% higher than the inner area beyond 290 nm from the surface, and the O concentration is also high, indicating that they are covered with chromium oxide. Figure 6 shows the XPS wide scan profiles of the non-welded and welded areas after coating. No difference was observed in the coating composition of the non-welded and welded areas after coating. Chromium oxide was formed on the stainless steel surface regardless of whether it was welded or not.
[0048] (7-2) Microstructure in the Depth Direction The cross sections of the non-welded and welded areas of the coated welded specimens were subjected to microstructural analysis by energy dispersive X-ray spectroscopy (TEM-EDS). Figure 7 shows images of the interface, middle, and surface. Figure 8 shows elemental mapping of the cross section. No oxide scale that occurs at the welded area is observed at the interface. Furthermore, although there is some unevenness at the interface between the coating and the base material (SUS304) at the welded area, as with the XPS evaluation, no difference in the coating composition between the non-welded and welded areas is observed. The thickness of the coating is 220 to 300 nm. Although voids of about 10 nm exist in the coating at the welded and non-welded areas, they are not connected.
[0049] 8. Hydrogen permeation mechanism FIG. 9 is an explanatory diagram of the hydrogen permeation mechanism in stainless steel that has been coated with the film of the present invention and has been welded. Hydrogen gas molecules adsorbed on the film (chromium oxide) surface are dissociated into atomic hydrogen. The dissociated hydrogen atoms diffuse into the film (chromium oxide) and the base material (SUS304). The diffused hydrogen atoms recombine on the surface on the low hydrogen partial pressure side and are released as hydrogen molecules. The coating of the present invention is composed of amorphous chromium oxide (see Non-Patent Documents 1 and 2), and it is presumed that the diffusion of hydrogen atoms is hindered by the pore interfaces present in the coating, and that the presence of many pore interfaces in the coating provides a certain inhibitory effect on the movement and diffusion of atoms at the interfaces. On the other hand, in the case of the stainless steel that has been welded and coated with the film of the present invention, the hydrogen permeability is reduced to 1 / 100, and it is clear that there are no pinhole defects through which hydrogen gas molecules can directly penetrate. The hydrogen barrier film is uniformly coated over the entire surface.
[0050] Furthermore, in the case of stainless steel that has been welded and coated with the coating of the present invention, no oxide scale is found at the welded part, and the oxide scale at the welded part is completely removed by the electrolytic polishing treatment of the present invention. This improves the smoothness of the welded part before coating, and enables uniform coating. As a result, the welded part can achieve hydrogen barrier properties equal to or better than those of non-welded parts.
[0051] 9. Summary (9-1) By increasing the viscosity of the electrolytic polishing solution, the smoothness of the surface of the workpiece (such as a welded test piece) is improved. By using an electrolyte (E3) consisting of phosphoric acid (50 vol%) and methanesulfonic acid (50 vol%), the surface roughness (S a ) was 1.5 nm, which was lower than the 19 nm without electrolytic polishing (T1). In addition, the surface roughness (S a ) This is also lower than 12.5 nm (E1) and 5.7 nm (E2). (9-2) By coating the welded test piece with a hydrogen barrier film, the hydrogen permeability (Φ) was increased to 2.02×10 -14 mol / (m 2 ·s·Pa 0.5 ), and the hydrogen permeability (Φ) of the welded test piece without the formation of a coating is 2.51×10-12 mol / (m 2 ·s·Pa 0.5 ), confirming that the material has hydrogen barrier properties. In addition, the hydrogen permeability (Φ) of the non-welded test piece was 3.50×10 -14 mol / (m 2 ·s·Pa 0.5 ) and it can be confirmed that even welded stainless steel has hydrogen barrier properties equal to or greater than those of stainless steel. (9-3) According to the XPS analysis, the thickness of the coating film is 290 nm, the chromium content is about 10 at% higher than the bulk material, and a chromium oxide film is formed by the hydrogen barrier film formation treatment. In addition, the EDS analysis shows that there is no segregation in the element (Cr, O) distribution. (9-4) Cross-sectional TEM observations have shown that the thickness of the chromium oxide film with hydrogen barrier properties is 220nm to 300nm, and pores of about 10nm are found in the film. These pores are not interconnected. The presence of many such pores allows the pore interfaces to act as hydrogen trapping sites and inhibit hydrogen diffusion. This provides the film with hydrogen barrier properties. [Industrial Applicability]
[0052] The present invention provides a method for producing welded stainless steel with excellent hydrogen barrier properties.
Claims
1. A mechanical polishing process in which the welded stainless steel surface is mechanically polished by flat grinding and buffing. an electrolytic polishing process in which the welded stainless steel surface, which has been mechanically polished, is electrolytically polished with an electrolytic polishing solution containing phosphoric acid and methanesulfonic acid; A hydrogen barrier film formation process in which a hydrogen barrier film is formed on electrolytically polished and welded stainless steel by the Inco method; A method for producing a welded stainless steel coated with a hydrogen barrier coating comprising: The arithmetic mean height S of the welded stainless steel portion subjected to the electrolytic polishing process in accordance with ISO 25178-6 a (nm) is 1.5 nm or less 1. A method for producing a welded stainless steel coated with a hydrogen barrier film, comprising the steps of:
2. 2. The method for producing a welded stainless steel coated with a hydrogen barrier film according to claim 1, characterized in that, in the electropolishing solution containing phosphoric acid and methanesulfonic acid, the phosphoric acid concentration is 25 to 50 vol % and the methanesulfonic acid concentration is 50 to 75 vol %.
3. the hydrogen barrier film forming step includes a film forming step of forming a chromium oxide film on a stainless steel surface by immersing the stainless steel surface in a treatment liquid comprising a mixed solution of chromic acid and sulfuric acid; a hardening treatment step of immersing the chromium oxide film formed in the film forming step in a treatment liquid consisting of a mixed solution of chromic acid and phosphoric acid to harden the chromium oxide film; a passivation treatment step of immersing the chromium oxide film hardened in the hardening treatment step in a treatment liquid containing a passivating agent to passivate the chromium oxide film; 2. The method for producing a welded stainless steel coated with a hydrogen barrier film according to claim 1, comprising:
4. The hydrogen permeability of the welded stainless steel coated with the hydrogen barrier film is 2.0×10 -14 mol / (m 2 ・s・Pa 0.5 ) ~ 3.5 x 10 -14 mol / (m 2 ・s・Pa 0.5 4. A method for producing a welded stainless steel coated with the hydrogen barrier coating according to claim 1, wherein the hydrogen barrier coating is a hydrogen barrier coating having a thickness of 100 nm or less.
5. 4. The method for producing a welded stainless steel coated with a hydrogen barrier film according to any one of claims 1 to 3, characterized in that the hydrogen barrier film of the welded stainless steel coated with a hydrogen barrier film in the hydrogen barrier film formation step has unconnected pores of about 10 nm in size that function as hydrogen trapping sites.
Citation Information
Patent Citations
Stainless steel structure with excellent resistance to hydrogen embrittlement and corrosion, and manufacturing method thereof
JP6869495B1
Electrolytic polishing solution, electrolytic polishing method for stainless steel using the same, and method for producing stainless steel with excellent corrosion resistance
JP7029742B1